Jane's Light Tanks and Armoured Cars - Christopher F. Foss (Jane's Publishing Company Limited, 1984)
Shows light tanks, jeeps, armored cars, amphibious vehicles, and scouts currently used by the world's armed forces, and provides information about the development, armament, and technical specifications of each vehicle.